2010
DOI: 10.1007/s00415-009-5439-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cerebral infarctions in a patient with Churg-Strauss syndrome

Abstract: Neurological manifestation of Churg-Strauss syndrome (CSS) is common and usually consists of peripheral neuropathy due to small-vessel vasculitis, while cerebral manifestation is less frequent. We report the case of a 77-year-old woman with multiple cerebral infarctions and hypereosinophilia. The presence of hypereosinophilia, asthma, sinusitis and vasculitis led to the diagnosis of CSS. As cerebral infarctions occurred monophasically and an elevation of heart enzymes was present, we assumed cardiac involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In EGPA, neurological manifestation is common, usually consisting of peripheral neuropathy due to small-vessel vasculitis, whereas cerebral manifestation is less frequent, especially when due to brain embolism [ 17 ]. The source of brain embolism includes the left ventricle and even the ascending aorta [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In EGPA, neurological manifestation is common, usually consisting of peripheral neuropathy due to small-vessel vasculitis, whereas cerebral manifestation is less frequent, especially when due to brain embolism [ 17 ]. The source of brain embolism includes the left ventricle and even the ascending aorta [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The source of brain embolism includes the left ventricle and even the ascending aorta [ 18 ]. However, according to one series of cases, none of the EGPA patients had any known cause in the heart that could account for cerebral/cerebellar infarcts [ 17 , 19 ]. Psychogios et al reported a case of EGPA in which multiple cerebral infarcts, along with purpuric skin rash, was the first manifestation of EGPA, although in the case of a 63-year-old female, no apparent findings suggestive of cardioembolism were detected on echocardiography [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous case series included brain infarcts as a manifestation or complication of Churg-Strauss syndrome in 3 patients [10]. One case report described intracerebral haemorrhage as a rare sequel of Churg-Strauss syndrome [11], and another reported an elderly woman with multiple cerebral infarctions and hypereosinophilia with assumed cardiac involvement and multiple cerebral infarctions due to cardiac embolism [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilic granulomatosis with polyangiitis (EGPA) causes bronchial asthma and allergic rhinitis as a preceding symptom and results in vasculitis accompanied with eosinophilia [1, 2]. In rare cases, EGPA is thought to exhibit multiple cerebral infarction in cortical, subcortical, and watershed areas, and mechanisms of vasculitis and special granules secreted by eosinophils have been considered [3]. Furthermore, because of the presence of left ventricular thrombus due to eosinophilic myocarditis, embolism is considered a cause, but the details are unknown [3].…”
Section: Introductionmentioning
confidence: 99%
“…In rare cases, EGPA is thought to exhibit multiple cerebral infarction in cortical, subcortical, and watershed areas, and mechanisms of vasculitis and special granules secreted by eosinophils have been considered [3]. Furthermore, because of the presence of left ventricular thrombus due to eosinophilic myocarditis, embolism is considered a cause, but the details are unknown [3].…”
Section: Introductionmentioning
confidence: 99%